Patients', physicians', nurses', and pharmacists' preferences on the characteristics of biologic agents used in the treatment of rheumatic diseases - Scalone, Luciana; Sarzi-Puttini, Piercarlo; Sinigaglia, Luigi; Montecucco, Carlomaurizio; Giacomelli, Roberto; Lapadula, Giovanni; Olivieri, Ignazio; Giardino, Angela Maria; Cortesi, Paolo Angelo; Mantovani, Lorenzo G; Mecchia, Monica (Patient preference and adherence, 2018)
To estimate preferences in relevant treatment characteristics evaluated by different groups involved in the management of patients with rheumatic diseases. We surveyed patients with rheumatic diseases, and rheumatologists, nurses, and pharmacists with experience in treatment with/provision of biologic drugs for these patients. Through a discrete choice experiment, participants evaluated 16 possible scenarios in which pairs of similarly efficacious treatments were described with six characteristics: 1) frequency of administration; 2) mode and place of administration; 3) manner, helpfulness, efficiency, and courtesy of health personnel; 4) frequency of reactions at the site of drug administration; 5) severity of generalized undesired/allergic reactions; and 6) additional cost. The direction and strength of preferences toward each characteristic level and the relative importance of each characteristic were estimated through a random-effects conditional logistic regression model. In total, 513 patients, 110 rheumatologists, 51 nurses, and 46 pharmacists from 30 centers in Italy participated. Characteristics 3, 4, and 6 were the most important for every subgroup; 1 was least important for patients and rheumatologists, 2 was least important for pharmacists, and 2 and 5 were least important for nurses. For characteristic 2, pharmacists preferred subcutaneous self-injection with a syringe; nurses preferred assisted infusion at an infusion center close to the patient's home; patients and rheumatologists preferred subcutaneous self-injection with a pen. The different preferences for some characteristics shown by the different groups can play an important role, together with purely clinical aspects, in the choice and consequent benefit of treatments, contributing also to a more satisfactory use of resources.